2007
DOI: 10.1186/1742-4682-4-26
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of label-structured cell population growth using CFSE distribution data

Abstract: Background: The flow cytometry analysis of CFSE-labelled cells is currently one of the most informative experimental techniques for studying cell proliferation in immunology. The quantitative interpretation and understanding of such heterogenous cell population data requires the development of distributed parameter mathematical models and computational techniques for data assimilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(99 citation statements)
references
References 39 publications
3
95
1
Order By: Relevance
“…The label-structured model (3.15) has been shown to provide an excellent fit to histogram data [21,79] and the model has been generalized (3.16) to permit the direct computation of cell numbers and division-specific division and death rates [23,46,74,79]. Though some comparison of the two different modeling approaches (describing cell numbers and fitting histogram data) has been done [56], it has not been immediately clear how to directly compare the distinct approaches in an impartial manner. Fortunately, the recent work on a 'division and label-structured population model' [46,74] has demonstrated how model (3.17) can be viewed as a unifying link between models of cell numbers and models of label dynamics (and thus histogram data).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The label-structured model (3.15) has been shown to provide an excellent fit to histogram data [21,79] and the model has been generalized (3.16) to permit the direct computation of cell numbers and division-specific division and death rates [23,46,74,79]. Though some comparison of the two different modeling approaches (describing cell numbers and fitting histogram data) has been done [56], it has not been immediately clear how to directly compare the distinct approaches in an impartial manner. Fortunately, the recent work on a 'division and label-structured population model' [46,74] has demonstrated how model (3.17) can be viewed as a unifying link between models of cell numbers and models of label dynamics (and thus histogram data).…”
Section: Discussionmentioning
confidence: 99%
“…The use of such a nonphysiological structure variable was suggested as early as 2000 for BrdU-based assays [30], and was first explored in the context of CFSE-based assays in [56]. More recent work [8,21,22,55,79] has consistently demonstrated that the label-structured PDE framework can accurately model the observed histogram data from a CFSE-based proliferation assay.…”
Section: Label-structured Pde Modelsmentioning
confidence: 99%
See 3 more Smart Citations